Evaluation of Rasbora spp. (Teleostei: Cyprinidae) from Sarawak and its Possible Cryptic Species - Aimi Wahidah, Aminan (Universiti Malaysia Sarawak(UNIMAS), 2018)
Cryptic diversity study is crucial as the constantly increasing number of cases involving natural ecosystem destruction in the extinction of species. The accurate diagnostic of cryptic species complexes need to be prioritized. Genus Rasbora hit the exact cryptic diversity occurrence as genus Rasbora can be considered as a catch-all group due to the lack of unique diagnostic characteristics per species. For solving the cryptic species in Rasbora, two approaches were used which are morphometric analysis and DNA barcoding analysis. There were 103 samples of Rasbora fishes used to conduct these methods. Altogether 24 morphometric and 11 meristic characteristics used for measurements and counts are recorded to determine the statistically significant differences of characteristics that are able to discriminate particular Rasbora species. Consequently cytochrome c oxidase subunit 1 (COI) gene was utilized as DNA barcode to discriminate the Rasbora specimens with the 33 Rasbora specimen tissues were used. The analyses confirmed the presence of eight Rasbora species. Morphometric analysis was able to determine the characteristics that contribute the most for species characterization which are pre-anal length for morphometric measurement and and pre-dorsal scales for meristic counts data respectively. The phylogenetic relationship of Rasbora was constructed whereby five major clades of Rasbora were created and were successfully mapped forming their own monophyletic clades. R. sumatrana and R. caudimaculata were clustered in the same clades and was found to be partially resolved. Hence, further study is needed to verify both Rasbora species and resolve the phylogenetic study of genus Rasbora from Sarawak.